Intentionality of a co-actor influences sensorimotor synchronisation with a virtual partner. - Mills, Peta F; Harry, Bronson; Stevens, Catherine J; Keller, Peter E; Knoblich, Guenther (Quarterly Journal of Experimental Psychology, 2019)
Interpersonal sensorimotor synchronisation requires individuals to anticipate and adapt to their partner's movement timing. Research has demonstrated that the intentionality of a co-actor affects joint action planning, however, less is known about whether co-actor intentionality affects sensorimotor synchronisation. Explicit and implicit knowledge of a synchronisation partner's intentionality may influence coordination by modulating temporal anticipation and adaptation processes. We used a computer-controlled virtual partner (VP) consisting of tempo-changing auditory pacing sequences to simulate either an intentional or unintentional synchronisation partner. The VP was programmed to respond to the participant with low or moderate degrees of error correction, simulating a slightly or moderately adaptive human, respectively. In addition, task instructions were manipulated so that participants were told they were synchronising with either another person or a computer. Results indicated that synchronisation performance improved with the more adaptive VP. In addition, there was an influence of the explicit partner instruction, but this was dependent upon the degree of VP adaptivity and was modulated by subjective preferences for either the human or the computer partner. Beliefs about the intentionality of a synchronisation partner may thus influence interpersonal sensorimotor synchronisation in a manner that is modulated by preferences for interacting with intentional agents.